Pemanfaatan Waqf Uang di Masa Pandemic Covid-19 Dalam Perspektif Maqasid Syariah - Nurlaili Nurlaili (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Money waqf can be used to overcome socio-economic problems that occur in Indonesia, this should be an opportunity to respond to the impact of the Covid-19 pandemic. As stated in the maqasid sharia concept, responding to a pandemic requires strategic and clear goals. This research paper aims to analyze whether the use of cash waqf has been optimally utilized or not at the time of covid 19, as well as cash waqf in terms of maqasid shariah. This study uses qualitative methods, using descriptive analysis in library research. The results of this study indicate that the use of cash waqf in Indonesia is still not optimal in overcoming the impact of this pandemic, there are several regions that still do not feel the distribution of the use of cash waqf. From the maqasid shari'ah point of view, the use of cash waqf is in accordance with As-Syatibi's description of the three mandatory concepts, namely